DESIGN DEVELOPMENT AND EVALUATION OF BILAYER TABLETS CONTAINING PARACETAMOL AS SR LAYER AND N-ACETYL CYSTEINE AS IR LAYER - Divya, Premanjali; Gupta, Dr. Manish Kumar; Sharma, Vijay (Journal of Biomedical and Pharmaceutical Research, 2018)
Preformulation study for understanding the various physico-chemical properties of the N-Acetyl Cysteinelone and its interaction with various excipients. Weigh accurately 10 mg of N-Acetyl Cysteine and transfer to 100 ml volumetric flask. The drug was dissolved in small quantity of water and the volume was made upto 100 ml to obtain a stock solution of 100 µg/ml. 1 ml of this stock solution was again diluted with water upto 10 ml to obtain a stock solution of 10 µg/ml. The resulting solution was scanned between 200 nm to 400 nm in a double beam UV/ Visible spectrophotometer. The melting points of the drugs were determined by open capillary method. Accurately weighed samples of each drug (2 mg) were transferred to aluminium pans and sealed. All samples were run at a heating rate of 10oC/min over a temperature range 40-43oC using Shimadzu DSC-60 Thermal Analyzer. The Infra-red spectroscopy of the sample was carried out to ascertain identity of the drugs. A pellet of approximately 1 mm diameter of each drug was prepared by compressing 3-5 mg of the drug with 100-150 mg of potassium bromide in KBr press (Model M-15, Techno Search Instruments).pH of 1% solution of N-Acetyl Cysteine and Paracetamol were determined by digital pH meter. Solvents such as water, alcohol, methanol and isopropyl alcohol were used for the solubility studies. Hydroxypropyl methyl cellulose which is a hydrophilic polymer is chosen for retarding the drug release as it has got both swelling and matrix-forming properties. Disperse HPMC E5 in about 45% IPA under stirring for 10 min. After proper dispersion, add MDC and solubilize HPMC E5 and keep under stirring for 15 min. In any rational design and evaluation of dosage forms for drugs, the stability of the active component must be major criteria in determining their acceptance or rejection. Keywords: N-Acetyl Cysteinelone,HPMC E5,bilayer tablets, SR layer, IR layer